2018
DOI: 10.17776/csj.443430
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polycyclic Aromatic Hydrocarbons Level in Commercial Turkish Milks

Abstract: In the present study, the presence of polycyclic aromatic hydrocarbons (PAHs) in commercial Turkish Milks was investigated. A total of 27 samples consisting of raw milk (n = 2), pasteurized milk (n = 5), UHT milk (n = 17) and also plant milk (n = 3) were analyzed for four EU marker polycyclic aromatic hydrocarbons (PAHs) by using a reversed phase high-performance liquid chromatography with fluorescence detection (HPLC-FLD). The method was in house validated using the validation parameters such as linearity, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The proportion of the sample exceeding the maximum residue limit (MRL) was 48%, 10%, and 16% in the rst, second, and third lactation periods, respectively ( PAH16 and PAH8 groups are the most common compounds in all lactation periods with 98% and 74%, respectively. This situation is similar to other studies; it was reported that PAH16 (Turaki Usman et al 2021) and chrysene (Kaçmaz 2018) were detected in all milk collected from Nigeria and Turkey. Because PAHs can be found widely in the atmosphere as well as in aquatic and terrestrial systems.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The proportion of the sample exceeding the maximum residue limit (MRL) was 48%, 10%, and 16% in the rst, second, and third lactation periods, respectively ( PAH16 and PAH8 groups are the most common compounds in all lactation periods with 98% and 74%, respectively. This situation is similar to other studies; it was reported that PAH16 (Turaki Usman et al 2021) and chrysene (Kaçmaz 2018) were detected in all milk collected from Nigeria and Turkey. Because PAHs can be found widely in the atmosphere as well as in aquatic and terrestrial systems.…”
Section: Resultssupporting
confidence: 92%
“…The animals may be exposed to them through drinking water, feeding, and/or inhalation (Adeniji et al, 2019). The PAHs concentrations indicate a range of < LOD-32.11 µg/kg which are much higher than concentrations reported for PAH4 in milk in Turkey (< LOD-0.14 µg/kg) according to Kaçmaz (2018). However, it is almost similar to the concentrations detected for PAH16 in milk collected from Nigeria.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation